AGE AND OBESITY INTERFERES IN MUSCLE HYPERTROPHY IN RATS UNDERGOING HIIT TRAINING - Rodrigues Jimenes, Diogo; Cândido, Fernanda; Rodrigues Teixeira Júnior, Nilton; Rinaldi, Wilson; Patrícia Barbosa, Carmem (Arquivos do Mudi, 2023)
Sarcopenic obesity is a condition characterized by the simultaneous presence of obesity and sarcopenia, which is the loss of muscle mass and function. Is a growing concern, especially among the elderly population, and it is important to address both obesity and sarcopenia through lifestyle modifications, such as exercise and proper nutrition, to improve overall health and quality of life. Our study aimed to evaluate the effect of HIIT training on the muscle fiber area of the EDL muscle in obese rats of different ages. For that, Wistar rats, 7 and 12 months old, submitted or not to a HFD diet were subjected to HIIT training, 3 times a week, on alternate days, for 8 consecutive weeks. After the euthanasia EDL muscles was collected and processed histologically. Our data showed that HIIT training was able to promote muscle hypertrophy even with consumption of this diet, indicating that practicing this exercise can stimulate protein synthesis even under conditions of obesity.